Childhood Conduct Problems and Other Early Risk Factors in Rural Adult Stimulant Users - Kramer, Teresa L. (2009)
CONTEXT: Understanding childhood risk factors associated with adult substance use and legal problems is important for treatment and prevention. PURPOSE: To examine the relationship of early substance use, conduct problems before age 15, and family history of substance abuse on adult outcomes in rural, stimulant users. METHODS: Adult cocaine and methamphetamine users (N=544) in rural Arkansas and Kentucky were interviewed. Data were analyzed using both bivariate analyses and multiple logistic and log-linear regression models, with dependent variables being any substance abuse/dependence, stimulant abuse/dependence, total number of arrests since age 18 and days incarcerated since age 18. FINDINGS: One-third reported three or more conduct disorder problems prior to age 15; half reported initiation of substances (excluding alcohol) before age 15; and 60% reported family history of substance problems. All three variables were associated with adult substance abuse/dependence but only the latter two were associated with stimulant abuse/dependence. CONCLUSIONS: This study highlights early risk factors for adult substance abuse/dependence among rural stimulant users.